2015
DOI: 10.1002/eji.201545615
|View full text |Cite
|
Sign up to set email alerts
|

NET formation can occur independently of RIPK3 and MLKL signaling

Abstract: The importance of neutrophil extracellular traps (NETs) in innate immunity is well established but the molecular mechanisms responsible for their formation are still a matter of scientific dispute. Here, we aim to characterize a possible role of the receptor‐interacting protein kinase 3 (RIPK3) and the mixed lineage kinase domain‐like (MLKL) signaling pathway, which are known to cause necroptosis, in NET formation. Using genetic and pharmacological approaches, we investigated whether this programmed form of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 21 publications
2
104
1
Order By: Relevance
“…However, two recent studies on the role of necroptosis in NETs induction present contrasting evidence for and against the requirements of necroptosis (Amini et al, 2016; Desai et al, 2016). Our data strengthens the argument that necroptosis is a separate cell death signalling cascade that is not required by neutrophils to induce NETosis.…”
Section: Discussionmentioning
confidence: 98%
“…However, two recent studies on the role of necroptosis in NETs induction present contrasting evidence for and against the requirements of necroptosis (Amini et al, 2016; Desai et al, 2016). Our data strengthens the argument that necroptosis is a separate cell death signalling cascade that is not required by neutrophils to induce NETosis.…”
Section: Discussionmentioning
confidence: 98%
“…Extracellular DNA was visualized by cell permeable fluorescent dyes, such as MitoSox Red or Syto 13 prior to fixation. SP‐D binding to the cell surface was analyzed by indirect immunofluorescence as previously described . Briefly, eosinophils pre‐incubated with either SP‐D or recombinant S‐nitrosothiol (SNO)‐SP‐D (5 μg/mL, both His‐Tagged), were seeded on glass coverslip, fixed with 4% paraformaldehyde and labeled by monoclonal anti‐His Ab (1:100; clone HIS.H8, ThermoFisher Scientific) overnight (4°C), and then with Alexa Fluor® 488 conjugated goat anti‐mouse secondary Ab (1:400; ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the problem of unspecific inhibition of various cell signaling pathways has been repeatedly brought up . Moreover, we and others have previously observed that slight modifications to experimental settings or conditions may lead to dissonant results . Therefore, the complexity of NETs formation mechanisms could be more easily studied if examined cells were amenable to genetic manipulations.…”
Section: Introductionmentioning
confidence: 99%